Microbial enhancement of nanocellulose isolation from sawn timber industrial wastes and fabrication of biocomposite membranes. (December 2022) - Zaki, Muhammad; Atiqah, M.S. Nurul; Khalil, H.P.S. Abdul; Ikram, Hira; Alfatah, Tata; Mistar, E.M.; Adisalamun, Adisalamun; Yahya, Esam Bashir
Abstract: In this study, we used for the first-time microbial pre-treatment to enhance the quality of nanocellulose isolation from sawn timber ( Hevea Brasiliensis ) industrial wastes. The microbial treated nanocellulose was then used in different concentrations as reinforcement in poly lactic acid (PLA) membranes and compared with conventionally isolated nanocellulose. Transmission electron microscopy (TEM) and particle size analysis showed that the diameter of microbial treated nanocellulose ranged from 4 to 22 nm while non-microbial treated had bigger diameter ranged between 25 and 100 nm. The membrane reinforced with microbial treated nanocellulose had a significantly higher water contact angle and absorbed less water than non-microbial treated nanocellulose. The optimum filler concentration was found to be 3 %, which exhibited tensile strength and modulus of 46.94 and 652.31 MPa respectively and 17.95 % elongation at break. Higher loading amount caused agglomeration phenomena, leading to reduce the nanocellulose-PLA interaction and thus, lowering the tensile strength, which was confirmed with AFM and SEM 3D analysis. Microbial treated nanocellulose has superior properties compared with the conventional one; it has great potentials as reinforcer in different packaging applications. Graphical Abstract: Unlabelled Image Highlights: Microbial pre-treatment significantly enhanced the quality of nanocellulose. The membrane reinforced with the enhanced nanocellulose. The optimum filler concentration was found to be 3 %. Less water was observed by enhanced nanocellulose based membranes.